A Critical Review of the Book “History, Culture &Civilization of Iran in the Buyid Dynasty” Ali Yahyaei - Ali Yahyaei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book “History, Culture &Civilization of Iran in the Buyid Dynasty” by Sadegh Hojjati is a detailed and relatively fluent account of the history of Iran and the Islamic world at the climax of Islamic civilization, which many scholars do not work on that period because of scarcity and Arabic linguistic references. The author appropriately organized the book into two parts: a political history (including ten chapters) and culture and civilization (including five chapters) and produced an acceptable work. But, neglecting some of the earlier sources and new research, not addressing some of the important issues such as religious politics and other aspects of foreign associations and some of the problems of segmentation or references in many paragraphs, various criteria in writing, and some inadequate judgments and probably inaccurate damaged the book to some extent. This article discusses the pros and cons of this book.